2011
DOI: 10.1021/es104082e
|View full text |Cite
|
Sign up to set email alerts
|

Biology-Based Modeling To Analyze Uranium Toxicity Data on Daphnia magna in a Multigeneration Study

Abstract: Recent studies have investigated chronic toxicity of waterborne depleted uranium on the life cycle and physiology of Daphnia magna. In particular, a reduction in food assimilation was observed. Our aims here were to examine whether this reduction could fully account for observed effects on both growth and reproduction, for three successive generations, and to investigate through microscope analyses whether this reduction resulted from direct damage to the intestinal epithelium. We analyzed data obtained by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
7
23
2
Order By: Relevance
“…Untangling an effect on maintenance cost or assimilation is, for example, particularly difficult when additional data on oxygen consumption are not available. Consequently, modeling work can fit equally well different MoA for a same contaminant, as observed for the effect of uranium on aquatic species (Augustine et al, 2012;Massarin et al, 2011;Goussen et al, 2015). In our study, the impact of BPA on v is the most suitable mode of action as it yields predictions particularly close to real values.…”
Section: Accepted Manuscript 43 Mode Of Action Of Imsupporting
confidence: 59%
“…Untangling an effect on maintenance cost or assimilation is, for example, particularly difficult when additional data on oxygen consumption are not available. Consequently, modeling work can fit equally well different MoA for a same contaminant, as observed for the effect of uranium on aquatic species (Augustine et al, 2012;Massarin et al, 2011;Goussen et al, 2015). In our study, the impact of BPA on v is the most suitable mode of action as it yields predictions particularly close to real values.…”
Section: Accepted Manuscript 43 Mode Of Action Of Imsupporting
confidence: 59%
“…They also reported a complementary study showing a loss of gut wall architecture, presence of large necrotic zones and an overall decrease in gut bacteria, in accordance with an effect on assimilation. In a similar way, Massarin et al (2011) analysed uranium toxicity data on D. magna showing a likely effect on assimilation based both on modelling of the growth and reproduction responses and histological analysis of uranium induced damage to the gut wall. The same kind of histological effects was observed on the earthworm Eisenia fetida exposed to soil contaminated with uranium (Giovanetti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of uranium toxicity data on Daphnia magna using deb theory concluded that assimilation decreased in response to water-borne exposure to U (Massarin et al, 2010(Massarin et al, , 2011. Their study showed that effects of uranium on growth and reproduction were captured equally well when assuming a decrease in assimilation or an increase in somatic maintenance in the first two generations, but that effects on the third generation were better characterized by a decrease in assimilation.…”
Section: Reproductive Toxicologymentioning
confidence: 99%